2011
DOI: 10.1002/mds.23903
|View full text |Cite
|
Sign up to set email alerts
|

Beyond nine years of continuous subthalamic nucleus deep brain stimulation in Parkinson's disease

Abstract: Deep brain stimulation of the subthalamic nucleus is an effective treatment for advanced Parkinson's disease. The benefits of bilateral subthalamic stimulation are well documented, and some studies reported outcomes with a follow-up of 5 to 6 years; nevertheless, few data are available beyond 5 years. We report a long-term prospective evaluation of 14 consecutive parkinsonian patients, treated by bilateral subthalamic stimulation for at least 9 years. Motor symptoms, activity of daily living, and motor complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
164
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 40 publications
26
164
1
6
Order By: Relevance
“…Our findings agree with what observed in other studies [6], [7] and [8], and could be chiefly explained by the progression of the disease over time [16]. While the cardinal PD symptoms keep on improving with stimulation, there is a progressive emerging of poorly levodopa-responsive symptoms, mainly axial symptoms, speech problems and postural instability.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings agree with what observed in other studies [6], [7] and [8], and could be chiefly explained by the progression of the disease over time [16]. While the cardinal PD symptoms keep on improving with stimulation, there is a progressive emerging of poorly levodopa-responsive symptoms, mainly axial symptoms, speech problems and postural instability.…”
Section: Discussionsupporting
confidence: 92%
“…STN-DBS efficacy on PD motor symptoms is well documented in the short-and medium-term, up to 5-6 years [4] and [5], while a few papers with a small number of examined patients addressed the long-term efficacy of this procedure [6], [7] and [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer series suggested that STN‐DBS cognitive effects do not influence quality of life (Contarino et al., 2007) or daily living activities (Zangaglia et al., 2012). Long‐term studies have shown that the proportion of STN‐DBS patients who converted to dementia was not different compared to those receiving medication at 2 years follow‐up (Zibetti et al., 2011). Overall, STN‐DBS does not seem to modify the cognitive evolution along the course of the disease (Rodriguez‐Oroz, Obeso, & Lang, 2005; Merola et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…From a different perspective, a study that evaluated the main limiting factors of activities of daily living (ADL) in patients undergoing stereotactic surgery with deep brain stimulation for the treatment of PD, showed that after nine years since the intervention, non-axial signs, including tremor, rigidity and bradykinesia, remained relatively stable. However, axial signs (postural instability and gait disorder) and NMS began to exert a growing negative effect, reflecting levels of functionality that were similar or worse than those observed before surgery 9 .…”
Section: Prevalence and Impact Of Non-motor Signs Of Parkinson's Diseasementioning
confidence: 98%